2023
DOI: 10.1021/acs.jctc.3c00620
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Molecular Hamiltonians into Hamiltonians of Modular cQED Processors

Ningyi Lyu,
Alessandro Miano,
Ioannis Tsioutsios
et al.

Abstract: We introduce a general method based on the operators of the Dyson-Masleev transformation to map the Hamiltonian of an arbitrary model system into the Hamiltonian of a circuit Quantum Electrodynamics (cQED) processor. Furthermore, we introduce a modular approach to programming a cQED processor with components corresponding to the mapping Hamiltonian. The method is illustrated as applied to quantum dynamics simulations of the Fenna-Matthews-Olson (FMO) complex and the spin-boson model of charge transfer. Beyond … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 74 publications
0
0
0
Order By: Relevance
“…Within this equation, the generator of dynamics is the molecular Hamiltonian. It has recently been shown that the molecular Hamiltonian can be mapped onto a polynomial of bosonic creation and annihilation operators of a single bosonic mode (SBM) . Thus, using this so-called SBM mapping allows for the simulation of chemical dynamics on a cQED device.…”
Section: Recent Developmentsmentioning
confidence: 99%
See 4 more Smart Citations
“…Within this equation, the generator of dynamics is the molecular Hamiltonian. It has recently been shown that the molecular Hamiltonian can be mapped onto a polynomial of bosonic creation and annihilation operators of a single bosonic mode (SBM) . Thus, using this so-called SBM mapping allows for the simulation of chemical dynamics on a cQED device.…”
Section: Recent Developmentsmentioning
confidence: 99%
“…Specifically, the SBM mapping makes it possible to transform an arbitrary k × k Hamiltonian matrix = prefix∑ α = 0 k 1 α = 0 k 1 H α α false′ | α α | which is represented in terms of the basis set {|α⟩} of choice, into the following elementary bosonic operators of a single qumode ( â , â † ), as follows: sbm = prefix∑ m = 0 k 1 n = 0 k 1 H n m n m where n m 1 ( k 1 ) ! 2 m ! n ! false( false) n normalΓ̂ k k 1 false( false) k 1 m …”
Section: Recent Developmentsmentioning
confidence: 99%
See 3 more Smart Citations